The value of eosinophil count in the diagnosis of preeclampsia among pregnant women attending the University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2021 - Yemataw Gelaw; Fikir Asrie; Muluken Walle; Zegeye Getaneh (BMC, 2022)
Abstract Background Currently, studies showed that eosinophil count had clinical significance in the diagnosis and prognosis of diseases. But, the clinical significance of eosinophil count in pregnancy specifically in preeclampsia (PE) is not well studied. The main objective of the present study was to assess the diagnosis value of eosinophils counts among pregnant women with PE. Methods A comparative cross-sectional study was conducted on a total of 126 pregnant women at the University of Gondar Comprehensive Specialized Hospital, using a convenient sampling technique. Socio-demographic and clinical data were collected by questionnaire and datasheet from patient's charts, respectively. A total of six ml of blood was collected from each study participant; three ml for complete cell count analysis using Sysmex XS-500i hematology analyzer and three ml for liver function tests using Humastar 200 chemistry analyzer. The data were entered into Epi-data and exported to SPSS 20 for analysis. The independent t-test was used for normally distributed data and, the Mann-Whitney U test was used for non-normally distributed data. Binary logistic regression and receiver operative curve analyses were also done to assess the diagnosis value of eosinophils count. P-value < 0.05 was considered statistically significant. Results The eosinophils count of PE pregnant women were significantly lower than the normotensive (NT) pregnant women (median (IQR): 50 (10-200) vs. 120 (60 - 270); (p = 0.002). The eosinophil count ≤ 55 cells/µL had an AUC of 0.66 (95% CI; 0.56-0.75) for diagnosis of PE with a sensitivity of 50.8%, specificity of 77.8%, and positive and negative predictive value of 69.6% and 61.3%, respectively. The abnormal AST and ALT results were significantly higher among PE pregnant women compared to NT pregnant women (AOR: 14.86; 95% CI: 4.97-44.4 and Fischer exact test p-value = 0.001, respectively). Conclusion The eosinophil count ≤ 55cells/µl had a reasonable/acceptable AUC which may use in the diagnosis of PE. AST and ALT were also significantly higher in PE pregnant women compared to NT pregnant women. Multicenter longitudinal studies with a large sample size are recommended to verify the role of eosinophil count in the diagnosis of PE.